Identity and home: Understanding the experience of people with advanced cancer. (May 2018) - Maersk, Jesper Larsen; Cutchin, Malcolm P.; la Cour, Karen
Abstract: The purpose of this study was to explore how the identity of people with advanced cancer is influenced by their experiences of living at home. A total of 28 in-depth interviews were conducted with 22 people with advanced cancer and four spouses. Grounded theory guided the collection and analysis of data. Home tours and associated field notes augmented the interview data. The analysis revealed that support of participants' identity was reflected in their abilities to live and occupy the home during daily activities, and in the ways the home and objects functioned as referents to themselves and their past. Threats to their identity ensued as the home environment became unmanageable during daily activities and as homecare professionals and assistive devices entered the home. By supporting people with advanced cancer in maintaining daily activities in the home and reducing changes in the home caused by homecare it is possible to reduce loss of identity. Highlights: Identity of people with advanced cancer is maintained by living in a home environment that is manageable. The home of people with advanced cancer is a place where their identity can be asserted. Assistive devices may disrupt continuity between past, present, and future identities. Relocating and maintaining the homeliness of the home is a way of coping with threats to identities.